IDENTIFIKASI LITOLOGI PADA DAERAH PANAS BUMI MENGGUNAKAN METODE RESISTIVITY KONFIGURASI WENNER-SCHLUMBERGER DI DESA GALUNG KABUPATEN BARRU - Ilyas, Mohamad; Sahara, Sahara; Wahyuni, Ayusari (JFT : Jurnal Fisika dan Terapannya, 2017)
Sub-surface analysis has been conducted to find out the lithology which includes the structure, the type of rock and the thickness of the geothermal layer of geothermal resources by using the geoelectric configuration method of Wenner-Schlumberger in Kalompie Hamlet, Galung Village, Barru sub-District, Barru District. The working principle of the geoelectric method is performed by injecting an electric current to the ground surface through a pair of current electrodes and measuring the potential difference with another pair of electrodes. The research was conducted in three trajectories with a trajectory length of 105 m and a spacing of 7 m electrodes. The result of the data interpretation was obtained by three materials that is sandy soil with resistivity value 0,095 - 4,05 Î©m have thickness 1 - 12 m, tuffed sandstone with resistivity value 4,05 - 39,7 Î©m having thickness 10 - 14 m, with a resistivity value of 39.7 - 547 Î©m with a thickness of 5 - 15 m, this rock is suspected as a rock cover on Kalompie hot water source area because it has a difficult nature to pass water (impermeabel). The geological structures of fault, anticline and syncline are not found in this research because the measurement path does not cut or pass through the path of geological structure.Â Keywords: geoelectric, Wenner-Schlumberger configuration, geothermal